Telerehabilitation with live-feed biomedical sensor signals for patients with heart failure: a pilot study - Tousignant, Michel (Cardiovasc Diagn Ther, 2019)
BACKGROUND: Integrating biomedical sensors to a telerehabilitation platform allowed clinicians to receive real-time transmissions of the electrocardiogram (ECG) signal, oxygen saturation, and heart rate during an exercise program. These clinical data could be helpful to adjust and personalize the intensity of exercises to each patient’s condition. The purpose of this study was to evaluate the feasibility and usefulness of biomedical sensors in telerehabilitation in patients with heart failure (HF). METHODS: Four participants with HF (mean age 66 years) followed the 12-week cardiac program using telerehabilitation, including sensors to monitor real-time vital signs during sessions. The exercise program included cardiovascular, strengthening and flexibility exercises. Participants were evaluated before the intervention and one month after the end of the program. Functional capacity was measured with Cardiopulmonary Exercise Testing (CPX), the 6-minute walk test (6MWT), and the sit to stand test (STST). Quality of life was objectified using the Kansas City Cardiomyopathy Questionnaire (KCCQ). RESULTS: Our main objective demonstrated that real-time biomedical sensors can be safely used by clinicians during a telerehabilitation session. Most participants showed a tendency to improve their physical capacities such as walking distance and lower limb muscular strength. As a main outcome of cardiac rehabilitation (CR), quality of life seems to improve after the 12-week intervention. CONCLUSIONS: This study proved the feasibility of using telerehabilitation with real-time biomedical sensors as an alternative or a complement to the conventional CR program. Use of sensors allowed a safe environment for the patient and an adequate and personalized exercise prescription. Limitation in one-to-one supervision must be challenged in future clinical trials to demonstrate that telerehabilitation could be efficient for cardiac patients requiring more individual supervision than group sessions in a gymnasium.